Assessment of fuel rate in specific operating conditions - Шаша, Ігор Костянтинович; Сікоринский, Віталій Валерійович (Technology audit and production reserves, 2014)
The analysis of estimated indicators, affecting fuel rate by armored vehicles in specific operating conditions is presented. Restrictions, inherent in the specifics of vehicles operation when performing service-combat missions are given. Ways of improving the existing mathematical model of fuel rate are proposed. The purpose of the research is to assess fuel rate dependence in specific operating conditions for the mathematical model improvement and further fuel rate calculation method development. To achieve this goal it was necessary to solve the following key problems: to assess the impact of major operational and structural factors on fuel rate in specific operating conditions; adopt restrictions, which will allow to improve the mathematical fuel rate calculation model, which unlike the existing considers the factors of specific operating conditions.